2007
DOI: 10.1002/pds.1463
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine in the first trimester and the prevalence of congenital malformations

Abstract: These more detailed paroxetine findings confirm previous findings of analyses of these data among women exposed to all types of antidepressants. The present findings are consistent with other recent results suggesting the possibility of a modestly increased occurrence of congenital malformations following first trimester exposure to paroxetine compared to other antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 12 publications
3
90
0
1
Order By: Relevance
“…4 In 2005, based on early results of two epidemiologic studies, the US Food and Drug Administration (FDA) warned healthcare professionals that early prenatal exposure to paroxetine may increase the risk of congenital cardiac malformations and reclassified it to pregnancy category D. 5 Most malformations in the early reports leading to the FDA warning were septal defects. Since then, several studies have evaluated the teratogenicity of SSRIs and other antidepressants [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , but considerable controversy remains as to whether this is a "serious concern or much ado about little" as noted in an editorial published with two of the reports. 13,1420 Existing studies have reported different associations, often in the context of multiple comparisons.…”
Section: Conclusion-resultsmentioning
confidence: 99%
“…4 In 2005, based on early results of two epidemiologic studies, the US Food and Drug Administration (FDA) warned healthcare professionals that early prenatal exposure to paroxetine may increase the risk of congenital cardiac malformations and reclassified it to pregnancy category D. 5 Most malformations in the early reports leading to the FDA warning were septal defects. Since then, several studies have evaluated the teratogenicity of SSRIs and other antidepressants [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , but considerable controversy remains as to whether this is a "serious concern or much ado about little" as noted in an editorial published with two of the reports. 13,1420 Existing studies have reported different associations, often in the context of multiple comparisons.…”
Section: Conclusion-resultsmentioning
confidence: 99%
“…Several studies [18][19][20][21][22] have shown an increased risk of VSDs in neonates exposed to paroxetine during the first trimester. This finding led the US Food and Drug Administration to advise women to avoid paroxetine during pregnancy if possible and to change pregnancy labeling from a category C to D. Paroxetine is the only SSRI whose pregnancy category labeling has changed.…”
Section: Discussionmentioning
confidence: 99%
“…Cole et al (2007) observed an increased risk for all malformations after the use of paroxetine (OR, 1.76; 95% CI, 1.18-2.64), but not for cardiovascular malformations (OR, 1.46; 95% CI, 0.74-2.88); they used an administrative database from a health care insurer and compared malformation rates with a cohort of mothers using other antidepressants. Only liveborn children with malformations were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, the manufacturer of paroxetine, a frequently used SSRI, issued a warning that preliminary analyses from safety data showed an increased risk of cardiovascular anomalies after use of paroxetine compared with use of other antidepressants (GlaxoSmithKline Clinical Trial Register, 2005). After this warning, several cohort studies were published on this association, but the results are inconclusive (Cole et al, 2007;Kallen and Otterblad 2007;Diav-Citrin et al, 2008;Merlob et al, 2009;Pedersen et al, 2009). Together, these cohort studies indicate that SSRIs do not have a major teratogenic effect.…”
Section: Introductionmentioning
confidence: 99%